Access to and returns from unpaid graduate internships - Angus Holford (University of Essex, Institute for Social and Economic Research (ISER), 2017)
We use the Destination of Leavers from Higher Education Survey (DLHE) to estimate the socio-economic gradient in access to unpaid internships among English and Welsh graduates six months after completing their first degree, and the return to this internship experience 3 years later in terms of salary, occupation, contract type and career satisfaction. We show a significant salary penalty at 3.5 years after graduation compared with those going straight into paid work or further study, but also that graduates from higher socio-economic status have an advantage in accessing internships while being significantly insulated from their negative effects.
Keywords: J24; J28; J31; 330; higher education; internships; human capital; job satisfaction